Chronic Myeloid Leukemia (CML) Complicated by Mixed Malaria Infection- An Unusual Presentation - Zahra, Kanwal; Naseem, Lubna (International Journal of Pathology, 2018)
Objective: To report an unusual case of Chronic Myeloid Leukemia (CML) undergoing chemotherapycomplicated by co- infection with Plasmodium vivax and Plasmodium falciparum.Case presentation: A 31 years Kashmiri male who was a known case of Philadelphia positive Chronic MyeloidLeukemia and on chemotherapy for last1 year, presented with high grade fever, left flank pain, vomiting andone episode of epistaxis. The oncologist suspected CML progressing to Accelerated phase or chemotherapeuticdrug (Tasigna) associated adverse effects leading to thrombocytopenia. He was diagnosed with mixed malarialinfection based on positive blood smear and bone marrow aspirate showing gametocytes of both PlasmodiumVivax and Plasmodium Falciparum. Patient was treated successfully with anti malarial drugs and showedmarked improvement in platelet count.Conclusion: It is suggested that malaria should be considered as a complicating factor in the patients ofhematological malignancies or those on chemotherapy in form of fever or thrombocytopenia, especially inmalaria- endemic areas.